Higher proportions of CD39+ tumor-resident cytotoxic T cells predict recurrence-free survival in patients with stage III melanoma treated with adjuvant immunotherapy. Issue 6 (10th June 2022) - Attrill, Grace Heloise; Owen, Carina N; Ahmed, Tasnia; Vergara, Ismael A; Colebatch, Andrew J; Conway, Jordan W; Nahar, Kazi J; Thompson, John F; Pires da Silva, Ines; Carlino, Matteo S; Menzies, Alexander M; Lo, Serigne; et al.
Abstract : Background: Adjuvant immune checkpoint inhibitor (ICI) immunotherapies have significantly reduced the recurrence rate in high-risk patients with stage III melanoma compared with surgery alone. However, 48% of anti-PD-1-treated patients will develop recurrent disease within 4 years. There is a need to identify biomarkers of recurrence after adjuvant ICI to enable identification of patients in need of alternative treatment strategies. As cytotoxic T cells are critical for the antitumor response to anti-PD-1, we sought to determine whether specific subsets were predictive of recurrence in anti-PD-1-treated high-risk patients with stage III melanoma. Methods: Associations with recurrence in patients with stage III melanoma were sought by analyzing resection specimens (n=103) taken prior to adjuvant nivolumab/pembrolizumab±low-dose/low-interval ipilimumab. Multiplex immunohistochemistry was used to quantify intratumoral CD8+ T-cell populations using phenotypical markers CD39, CD103, and PD-1. Results: With a median follow-up of 19.3 months, 37/103 (36%) of patients had a recurrence. Two CD8+ T-cell subpopulations were significantly associated with recurrence. First, CD39+ tumor-resident memory cells (CD39+CD103+PD-1+CD8+ (CD39+ Trm)) comprised a significantly higher proportion of CD8+ T cells in recurrence-free patients (p=0.0004). Conversely, bystander T cells (CD39−CD103−PD-1−CD8+) comprised a significantly greater proportion of T cells in patients who developed recurrence (p=0.0002). Spatial analysis identified that CD39+ Trms localized significantly closer to melanoma cells than bystander T cells. Multivariable analysis confirmed significantly improved recurrence-free survival (RFS) in patients with a high proportion of intratumoral CD39+ Trms (1-year RFS high 78.1% vs low 49.9%, HR 0.32, 95% CI 0.15 to 0.69), no complete lymph node dissection performed, and less advanced disease stage (HR 2.85, 95% CI 1.13 to 7.19, and HR 1.29, 95% CI 0.59 to 2.82). The final Cox regression model identified patients who developed recurrence with an area under the curve of 75.9% in the discovery cohort and 69.5% in a separate validation cohort (n=33) to predict recurrence status at 1 year. Conclusions: Adjuvant immunotherapy-treated patients with a high proportion of CD39+ Trms in their baseline melanoma resection have a significantly reduced risk of melanoma recurrence. This population of T cells may not only represent a biomarker of RFS following anti-PD-1 therapy, but may also be an avenue for therapeutic manipulation and enhancing outcomes for immunotherapy-treated patients with cancer.